1997
DOI: 10.1097/00005768-199704000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance analysis: evaluation of leg-to-leg system based on pressure contact foot-pad electrodes

Abstract: Conventional single frequency bioimpedance analysis (BIA) systems require technician placement of arm and leg gel electrodes, a suitable location for recumbent measurements, and a separate measurement of body weight. The aim of this study was to evaluate a new single frequency 50 KHz leg-to-leg bioimpedance analysis (BIA) system combined with a digital scale that employs stainless steel pressure-contact foot pad electrodes for standing impedance and body weight measurements. Healthy adults were evaluated for 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
181
0
4

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 252 publications
(194 citation statements)
references
References 17 publications
9
181
0
4
Order By: Relevance
“…The regression coefficient of 0.56 is close to 0.6 and compares to other studies which found the value to be 0.66 (Nunez et al, 1997;Bell et al, 1998). The intercept of 5.9 is larger than anticipated.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The regression coefficient of 0.56 is close to 0.6 and compares to other studies which found the value to be 0.66 (Nunez et al, 1997;Bell et al, 1998). The intercept of 5.9 is larger than anticipated.…”
Section: Discussionsupporting
confidence: 79%
“…The intercept of 5.9 is larger than anticipated. The intercepts in other studies have been 0.65 (Bell et al, 1998) and 1.93 (Nunez et al, 1997). Another study in children with Prader Willi syndrome did find a similar regression coefficient (Davies, 1992).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations